AN INVESTIGATION OF THE CONSTRUCTION OF THE ENGLISH FINAL TESTS AND THE TESTS' COMPLIANCE WITH THE OBJECTIVES OF THE PROGRAM : A Case Study at Three Primary Schools in Purworejo - Pasmuji, Sugeng (2009)
English teachers are those who are central in developing and conducting English test as one of the teacher's roles in educational duty is taking part as an assessor. Teachers, consequently, need to have capability in constructing quality English tests for their students. However, in some places in Indonesia, sometimes it is found that English tests constructed by the teachers are erroneous and contain some mistakes, even not valid. In consideration with this condition, this study particularly attempts to investigate descriptively how do the teachers construct the final English tests for the sixth grades primary school students in Purworejo in 2008/2009 and to what extent do the tests comply with the objectives of the English program. The study was addressed to answer the two research questions; (1) What steps do the teachers do in constructing the final tests on English for the sixth grades primary school students?; and (2) To what extent do the English final tests comply with the objectives of the English program conducted in the schools? To answer these research questions, the study used qualitative descriptive approach by applying open-ended interview and documents as the instruments for obtaining the data. There were three English teachers who had been teaching English in three different elementary schools in Purworejo who were purposively selected as the respondents of this study. When the study was conducted, they were constructing the English final tests for the students of the sixth grade elementary schools. The first research questions was answered through analyzing the interview transcriptions in which it was found that all of the respondents did not conduct the stage of pre-testing of the tests' batteries they made. All of the respondents stated that the time constraint was the cause of it, besides that they needed adequate support and facility from the schools such as test's schedule, proctors, fund, and students as test-takers. The findings of the document analysis of the syllabuses and the items of the tests show that some of the items of the tests did not represent the language elements (vocabulary and grammar) involved in the syllabuses. The absence of the pretest's result and analysis of the pretest's result possibly made the teachers impossible to revise the tests' errors. The conclusion of the study shows that constructing an English quality test requires the test writer to follow all the steps of test construction proposed by the theories. Therefore, English teachers are suggested to follow all the steps of test construction proposed by the theories periodically in constructing English tests. In order to help the teachers to construct quality English tests well, the principals of the schools are also suggested to facilitate the process of test construction well, for example, by managing test's schedule and providing proctors, fund, and students as the test-takers.